Metacomunidade e otimização do biomonitoramento da biodiversidade aquática de riachos tropicais - Faquim, Ruan Carlos Pires (2021)
Terrestrial ecosystems are increasingly impacted by anthropogenic changes, especially on vegetation cover, which causes deep changes in aquatic ecosystems, especially freshwater. The impacts are increasingly cumulative and multiple spatial scales, causing changes in structure, productivity and consequently in the entire chain, impacting abundance, richness and functional diversity. In an aquatic metacommunity, the species are different and can serve as a basis for the structural determinants of the community, for this reason in this work we evaluate aquatic communities subjected to different environmental changes and impacts, within and around the National Forest of Silvânia, Goiás. Thus, we structured the Thesis into three chapters, in CHAPTER I we assess how stream fish communities are affected by environmental and spatial factors through the deconstruction of the metacommunity, based on characteristics related to dispersal. Then, we use variation partitioning techniques to test the relative effects of local, spatial, and landscape environmental factors. The total abundance of species was weakly explained by environmental and spatial variables. The community structure of small and fast-flowing nectobenthic fish, in turn, was explained by the environment. As well, large and slowwater nectobenthic fish were explained by spatial variables, and the landscape was explained by slowwater fish with different dispersal capabilities. In CHAPTER II we use different biological groups and their congruences to identify the possibility of monitoring aquatic ecosystems. We evaluated whether taxonomy, numerical resolution and congruence between different taxa can be used to optimize cost and time for biomonitoring. For this purpose, we used Mantel and Procrustes analyses. The results showed that taxonomic levels and numerical resolutions were strongly correlated across all taxonomic groups (r>0.70), but not across biological groups. Different sets of environmental variables explained different compositions of different biological groups. We conclude that the use of groups as bioindicators is more informative through higher taxonomic levels with occurrence data, but that multi-rate assessments provide additional information in biomonitoring. In CHAPTER III we evaluate the direct and indirect effects of landscape, local environmental and productivity variables on the taxonomic and functional richness of the fish community (Rao's quadratic entropy). We built a theoretical model using structural equation modeling. Our results indicated a strong relationship between environmental variables and productivity on richness and functional diversity. Furthermore, the direct and indirect effects indicated that the preservation of the natural environment is really linked to better conditions of richness and functional diversity of the fish community.